Aboriginal stone-walled intertidal fishtrap morphology, function and chronology investigated with high-resolution close-range Unmanned Aerial Vehicle photogrammetry. (August 2018) - Kreij, Anna; Scriffignano, Jason; Rosendahl, Daniel; Nagel, Texas; Ulm, Sean
Abstract: Stone-walled intertidal fishtraps surround the Australian coastline and are among the largest structures built by Indigenous Australians. Globally, fishtraps are considered important elements in food production, domestication, territoriality and ceremonial landscapes, yet the level of detail in documentation is highly varied and scholarly fishtrap knowledge sparse. Comparative analysis is currently restricted by a lack of detail and reproducibility in recording, hindering analysis of morphology, function and chronology. In this study we employ high-resolution close-range Unmanned Aerial Vehicle (UAV) photogrammetry and a suite of spatial information analytical techniques to investigate the Kaiadilt Aboriginal stone-walled intertidal fishtraps of Sweers Island, southern Gulf of Carpentaria, Australia. Tidal inundation modelling is undertaken to assess (1) fishtrap working range, (2) individual and simultaneous trap function, (3) seasonal functionality and (4) chronology based on function relative to sea-level history. Thirteen fishtraps were identified in the study area, ranging from 38 m to 287 m in length. Flow accumulation indicates that shape and placement of fishtraps reflects underlying topography. Inundation modelling shows that all fishtraps operate most efficiently at present mean-sea level (PMSL), indicating construction in the last 3500 years. Quantitative recording techniques, analytical procedures and terminology developed in this study provide an opportunity to improve approaches to recording large-scale stone features and standardise documentation of stone-walled intertidal fishtrap sites. Graphical abstract: Image 1 Highlights: High-resolution UAV photogrammetry identifies 13 fishtraps on Sweers Island. Fishtrap working range established using high-resolution DEM (2 cm 2 ). Past sea-level inundation modelling establishes a maximum age of 3500 years. Quantitative GIS analysis provides basis for objective fishtrap identification. UAV photogrammetry recommended as a site recording and monitoring technique.